1981
DOI: 10.1288/00005537-198105000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The acoustic reflex test in cochlear and eighth nerve pathology ears

Abstract: The clinical interpretation of acoustic reflex test results in ears with sensorineural impairment should be based on a consideration of three characteristics of the response: the reflex threshold hearing level, the reflex threshold sensation level, and the decay of the reflex. Examination of results in 152 ears with cochlear pathology and in 152 ears with acoustic tumor indicated that in some cases the combination of characteristics may be contradictory as to site of lesion. Regarding a contradictory response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

1983
1983
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 10 publications
2
2
0
2
Order By: Relevance
“…The most sensitive (85 to 97 percent) procedures were ABR audiometry, acoustic reflexes, and BCL audiometry. Sensitivity results for BCL audiometry and acoustic reflex measures agree with the findings of most previous investigators (Hayes, 1980;Johnson, 1977;Joseyet al, 1980;Olsen et al, 1975;Sanders et al, 1981;Sheehy and Inzer, 1976;Thomsen and Terkildsen, 1975;Turner, 1981). However, a sensitivity index of 85 percent for acoustic reflexes is less than results (95 to 100 percent) reported by Liden and Korsan-Bengtsen (1973) and by Anderson et al (1970).…”
Section: Sensitivitysupporting
confidence: 89%
See 1 more Smart Citation
“…The most sensitive (85 to 97 percent) procedures were ABR audiometry, acoustic reflexes, and BCL audiometry. Sensitivity results for BCL audiometry and acoustic reflex measures agree with the findings of most previous investigators (Hayes, 1980;Johnson, 1977;Joseyet al, 1980;Olsen et al, 1975;Sanders et al, 1981;Sheehy and Inzer, 1976;Thomsen and Terkildsen, 1975;Turner, 1981). However, a sensitivity index of 85 percent for acoustic reflexes is less than results (95 to 100 percent) reported by Liden and Korsan-Bengtsen (1973) and by Anderson et al (1970).…”
Section: Sensitivitysupporting
confidence: 89%
“…Finally, the remaining diagnostic procedure, PI-PB functions, was of intermediate sensitivity (65 percent). This finding agrees with the results of Liden and Korsan-Bengsten (1975), Jerger and Jerger (1975b), Dirks et al (1977), and Sanders et al (1981). However, Bess et al (1979) and Turner (1981) found a substantially higher sensitivity index (89 to 94 percent) for PI-PB functions in their series of patients.…”
Section: Sensitivitysupporting
confidence: 88%
“…33; GrasonStadler Instruments, Littleton, MA) was used to measure the stapedial reflex threshold. The recruitment phenomenon was defined as being present when the difference between the stapedial reflex and pure-tone thresholds was B/60 dB [8].…”
Section: Audiological Testmentioning
confidence: 99%
“…It is known that in the case of retrocochlear pathology, no AR or elevated ART ("Metz negative") or no recruitment in loudness function is often observable. A strong correlation between the results of the Metz test and loudness function has been confirmed by many authors [11,17,23]. One possible hypothesis to explain this positive relation between the AR and loudness function might be that some common neuronal informa-9 Fig.…”
Section: Discussionmentioning
confidence: 57%